PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITES PADA MATA PELAJARAN INFORMATIKA DI SMA RLA IIBS SOLOK SEMESTER GENAP TAHUN AJARAN 2025/2026 - Chintya Permata Vadira; Wijaya, Indra; Radyuli, Popi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop interactive learning media based on Google Sites for the Informatics subject of Grade X students at SMA RLA IIBS Solok and to examine the feasibility of the developed media in terms of validity, practicality, and effectiveness. The learning media was developed as an effort to enhance the use of digital technology in the learning process and to encourage students’ independent learning. The research method employed was Research and Development (R&D) using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 32 Grade X students of SMA RLA IIBS Solok. The results of the validity test based on expert judgments showed that the Google Sites–based interactive learning media obtained a percentage score of 94.67%, categorized as very valid, indicating that it is appropriate for use in Informatics learning. Furthermore, the practicality test conducted with students resulted in a percentage of 87.92%, categorized as very practical, indicating that the learning media is easy to use and understand. Meanwhile, the effectiveness test showed a percentage of 87.81%, categorized as very effective, indicating that the use of the learning media supports the achievement of learning objectives and improves students’ understanding of Informatics material. Based on these results, it can be concluded that the developed Google Sites–based interactive learning media meets the criteria of validity, practicality, and effectiveness and is therefore suitable to be used as an alternative learning media for Grade X Informatics at SMA RLA IIBS Solok.